Intrahepatic cholestasis of pregnancy - Yanque-Robles, Omar F. (2020)
The intrahepatic cholestasis of pregnancy (ICP) is characterized by pruritus in the pregnant and elevated levels of serum bile acids, in addition it is associated with increased obstetric events such as preterm labor, meconium stained amniotic fluid and intrauterine fetal death. Its incidence is variable, being the South American and Asian countries, where the highest rates are reported. There is no known cause, but there are risk factors as well as well-studied genetic defects. The diagnosis should help to its classification, an early onset of ursodeoxycholic acid (UDCA) and a counseling regarding complications and termination of pregnancy.